Dewang Mehta: collected thoughts - Dewang Mehta (1962-2001) (Dewang Mehta foundataion trust, 2016)
Dewang Mehta: collected thoughts / Dewang Mehta (1962-2001). -- Mumbai: Dewang Mehta foundataion trust, 2016 920 M498 No. of Copies : 1